IL-15 Fosters Age-Driven Regulatory T Cell Accrual in the Face of Declining IL-2 Levels - Raynor, Jana (Frontiers Media S.A., 2013)
We and others have shown that regulatory T cells (T(reg)) accumulate dramatically with age in both humans and mice. Such T(reg) accrual contributes to age-related immunosenescence as they reduce the response to tumors and parasite infection. While we reported earlier that aged T(reg) have decreased expression of the pro-apoptotic molecule Bim and germline deletion of Bim promoted earlier accumulation of T(reg), it remains unclear whether the effects of Bim are: (i) T(reg) intrinsic and (ii) dominant to other BH3-only pro-apoptotic molecules. Further, the mechanism(s) controlling Bim expression in aged Treg remain unclear. Here we show that T(reg)-specific loss of Bim is sufficient to drive T(reg) accrual with age and that additional loss of the downstream apoptotic effectors Bax and Bak did not exacerbate T(reg) accumulation. Further, our results demonstrate that a subpopulation of T(reg) expands with age and is characterized by lower expression of CD25 (IL-2Rα) and Bim. Mechanistically, we found that IL-2 levels decline with age and likely explain the emergence of CD25(lo)Bim(lo) T(reg) because T(reg) in IL-2(−/−) mice are almost entirely comprised of CD25(lo)Bim(lo) cells, and IL-2 neutralization increases CD25(lo)Bim(lo) T(reg) in both young and middle-aged mice. Interestingly, the T(reg) population in aged mice had increased expression of CD122 (IL-2/IL-15Rβ) and neutralization or genetic loss of IL-15 led to less T(reg) accrual with age. Further, the decreased T(reg) accrual in middle-aged IL-15(−/−) mice was restored by the additional loss of Bim (IL-15(−/−)Bim(−/−)). Together, our data show that aging favors the accrual of CD25(lo) T(reg) whose homeostasis is supported by IL-15 as IL-2 levels become limiting. These data have implications for manipulating T(reg) to improve immune responses in the elderly.